PENYUSUNAN POLA PERJALANAN DI DESA WISATA TIPANG KECAMATAN BAKTIRAJA KABUPATEN HUMBANG HASUNDUTAN - Elita Putri Sari Rangkuti (Akademi Pariwisata Darma Agung, 2023)
This study aims to compile patterns of tourist trips in Tipang Tourism Village, Baktiraja District, Humbang Hasundutan Regency. The method used is a qualitative method with data collection techniques through in-depth interviews and direct observation. The selected respondents were tourists who had visited Tipang Tourism Village, homestay owners, and local people who were involved in tourism management. The results of the study show that Tipang Tourism Village has considerable tourism potential, especially in terms of natural and cultural tourism. Based on the results of interviews and observations, the pattern of tourist trips in Tipang Tourism Village can be structured as follows: tourists begin by visiting natural attractions such as waterfalls and tea gardens, then continue to cultural attractions such as traditional houses and places of worship, and end with activities culinary and shopping in traditional markets. The preparation of this travel pattern can be a reference for tourism managers in Tipang Tourism Village to improve existing tourism infrastructure and facilities, as well as improve the quality of service to tourists. In addition, the results of this study can also be used as a reference for other researchers who are interested in developing tourism in similar areas.